Sacred Sites Protection and Indigenous Women’s Activism: Empowering Grassroots Social Movements to Influence Public Policy. A Look into the “Women of Standing Rock” and “Idle No More” Indigenous Movements - Gottardi, Francesca (Religions, 2020)
Religion and public policy are interconnected across a variety of issues. One aspect where this linkage has been understudied is religion and Indigenous sacred sites protection. This article aims to address this gap by analyzing how Indigenous women’s activism advances this cause. The focus is on how Indigenous Peoples, specifically women, use grassroots activism to provoke change on public policy in the context of the protection of Indigenous sacred sites. Two case studies are used to illustrate this concept: the American “Women of Standing Rock” and the Canadian “Idle No More” grassroots social movements. My analysis draws from interpretative methods. Interpretative research revolves around the concept of individuals as active producers of meaning. The women-led grassroots social movements at issue highlight a fundamental lack of awareness of the historical and current struggles of Indigenous Peoples, both in the US and Canada. Modern technologies and social media provide democratic means for grassroots social movements to be heard and empowered. The growing movement by Indigenous women to assert their rights, and their quest for self-determination in land use and sacred sites protection create a positive discourse that advances Indigenous women’s position in crossing the obstacles onto “institutional places of privilege,” hence influencing public policy.